The implications of mid‐latitude climate extremes for North American migratory bird populations - La Sorte, Frank A.; Hochachka, Wesley M.; Farnsworth, Andrew; Dhondt, André A.; Sheldon, Daniel; Peters, D. P. C. (Ecosphere (Washington, D.C), 2016)
Mid‐latitude climate extremes are projected to increase in frequency under global climate change. How this may affect migratory bird populations is not well understood. The mid‐latitudes of North America experienced an extreme warming event during March 2012 that advanced the spring phenology of ecological productivity, resulting in lower levels of productivity during the summer. Here, we test the predictions that: (1) short‐distance migratory birds, due to geographic proximity and more flexible migratory behavior, should advance their spring migration phenology; and (2) breeding populations, due to lower summer productivity, should have reduced occurrences. We used occurrence data for 353 bird species from the eBird database to calculate weekly occurrence anomalies for 2012 relative to the 2010–2014 average. We identified species having unusually large positive occurrence anomalies during March 2012 and species having unusually large negative occurrence anomalies during July–August 2012. For each category, we summarized migration strategies, geographic distributions, and annual associations with temperature and ecological productivity. Short‐distance migrants whose winter and breeding ranges intersect the mid‐latitudes advanced their spring migration phenology during March (n = 21). Long‐distance migrants whose winter and breeding distributions were weakly associated with the mid‐latitudes had lower occurrences during the summer (n = 32). Five species were shared between the two categories. Within species’ winter ranges, temperature and ecological productivity were higher than expected during March; within species’ breeding ranges, ecological productivity was lower than expected during the summer. These differences were strongest for the 21 short‐distance migrants. Following our expectations, mid‐latitude climate extremes and associated ecological consequences broadly affected avian migration and breeding activities within the region. Our findings suggest short‐distance migrants are more flexible and resilient, whereas populations of long‐distance migrants are at a distinct disadvantage, which may intensify if the frequency of these events increases.